Changes in physical activity during a one-year weight loss trial with liraglutide vs placebo in participants with knee osteoarthritis: Secondary analyses of a randomised controlled trial. Issue 2 (June 2022) - Bartholdy, Cecilie; Overgaard, Anders; Gudbergsen, Henrik; Bliddal, Henning; Kristensen, Lars Erik; Henriksen, Marius
Abstract: Objective: To assess if a change in physical activity occurred after a one-year weight loss period on either liraglutide or placebo in patients with knee osteoarthritis (OA) and overweight. Method: This is secondary analysis of a one-year weight loss trial, with participants randomised (1:1) to either liraglutide 3 ​mg/day or placebo. The main outcome was change in physical activity (min/day) after one year assessed by accelerometer. Physical function was assessed using the Knee Injury and Osteoarthritis Outcome Score (KOOS), function subscale with 100 indicating no disability and 0 indicating extreme disability. Analyses were done on the modified intention to treat population defined as complete baseline accelerometer data. Results: A total of 135 participants were analysed (66 liraglutide; 69 placebo). Daily physical activity time did not change in either group (liraglutide: 15.8 ​min/day; placebo: 14.2 ​min/day; mean difference 1.6 ​min/day (95%CI -16 to 19; P ​= ​0.90)). The liraglutide group lost −4.1 ​kg more than placebo (95% CI -6.0 to −2.1; P ​< ​0.0001) and improved in KOOS function 3.8 points more than placebo (95% CI 0.9 to 6.7; P ​= ​0.01). Conclusion: Despite better outcomes on body weight and self-reported physical functioning liraglutide did not induce changes in physical activity over one year in individuals with knee OA.